FINANCIAL PROBLEMS AND OPPORTUNITIES OF THE DEVELOPMENT OF THE EDUCATION SYSTEM - Dusanov Salim Mamarasulovich (Scholar Express Journals, 2026)
The article presents the competitive environment, financial resources, financing issues, problems and their importance in the education system. At the same time, analytical approaches to the importance, role and effectiveness of financial resources in developing a competitive environment in educational institutions, and the basics of implementing new financing models are presented
Keywords: Education system; financing; competitive environment; improvement